A utilização das TDICs como estratégia de ensino e seus desafios ao processo de aprendizagem - Limeira, Linda Gabrieli da Silva (2020)
Digital technologies bring about changes in society. As a result, facilitated access to information and technological advances have suggested transformations in the area of ​​education. In this sense, this research aims to understand the importance of digital information and communication technologies in the classroom as a tool that helps in the teaching and learning process, making it meaningful and pleasurable for both the teacher and the student. Within this perspective, the study was developed through bibliographic research, using studies by Freire (2013), Lévy (1999), Santaella (1997), Veen and Vrakking (2009), among other scientific works on the subject. After the readings carried out, it was found that educational paradigms can be transformed starting with the awareness of the educational potential of textbooks, literary books, but also of the smartphone, tablets, computers and the different languages ​​that compose and motivate and they amuse children and young people, which consequently help in their integral formation.